Effectiveness of post-match recovery strategies in rugby players. Issue 3 (27th February 2006) - Gill, N D; Beaven, C M; Cook, C
Abstract : Objectives: To examine the effectiveness of four interventions on the rate and magnitude of muscle damage recovery, as measured by creatine kinase (CK). Methods: 23 elite male rugby players were monitored transdermally before, immediately after, 36 hours after, and 84 hours after competitive rugby matches. Players were randomly assigned to complete one of four post-match strategies: contrast water therapy (CWT), compression garment (GAR), low intensity active exercise (ACT), and passive recovery (PAS). Results: Significant increases in CK activity in transdermal exudate were observed as a result of the rugby match (p<0.01). The magnitude of recovery in the PAS intervention was significantly worse than in the ACT, CWT, and GAR interventions at the 36 and 84 hour time points (p<0.05). Conclusions: An enhanced rate and magnitude of recovery was observed in the ACT, CWT, and GAR treatment groups when compared with the PAS group. Low impact exercise immediately post-competition, wearing compression garments, or carrying out contrast water therapy enhanced CK clearance more than passive recovery in young male athletes.